Implementation of Subsidized Fertilizer Policy in Kotamobagu City - Mifta, Fenty Dilasandi; Masengi, Evi Elvira; Pangkey, Itje (Technium Social Sciences Journal, 2024)
The objectives of this research are 1) to know, analyze, and describe the Implementation of Subsidized Fertilizer Policy in Kotamobagu City; 2) To find out and analyze and describe the factors that influence the Implementation of Subsidized Fertilizer Policy in Kotamobagu City. This research uses qualitative research methods with data collection techniques in the form of in-depth interviews, observation, and documentation studies. In this study, the focus of research is the implementation of subsidized fertilizer policies for farmers in Kotamobagu City with sub-focus research on sufficiency, equity, and accuracy. Informants in this study were determined using purposive sampling. The results showed that the implementation of the fertilizer policy in Kotamobagu City has not been effective. The influencing factors are 1) fertilizer distribution is often late and uneven distribution, 2) The distribution of subsidized fertilizers is no longer realized based on the Group Needs Definitive Plan (RDKK) as well as weak coordination and lack of active role in the preparation and implementation of the Group Needs Definitive Plan (RDKK), and 3) The inaccuracy of fertilizer availability is detrimental to farmers. Therefore, the recommendations of this study are 1) strengthen distribution supervision, 2) increase the role of farmer groups, and 3) strengthen collaboration between stakeholders: local government, farmer groups, distributors, and other related parties.